# The value of $\sin {20^0}\sin {40^0}\sin {60^0}\sin {80^0}$ is

$\left( A \right)$. $\dfrac{{ - 3}}{{\sqrt {16} }}$

\[\left( B \right)\]. $\dfrac{5}{{\sqrt {16} }}$

$\left( C \right)$. $\dfrac{3}{{\sqrt {16} }}$

$\left( D \right)$. $\dfrac{{ - 5}}{{\sqrt {16} }}$

Last updated date: 16th Mar 2023

•

Total views: 306.9k

•

Views today: 2.89k

Answer

Verified

306.9k+ views

Hint: In the above problem the trigonometric product to sum identities should be used. The identity to be used is to be determined by inspection so that the result gives angle with general known trigonometric ratio.

Given in the problem, we need to find value of the expression

$\sin {20^0}\sin {40^0}\sin {60^0}\sin {80^0}$ …………………………….. (1)

We need to group terms so that using a product to sum trigonometric formula gives angles whose trigonometric value is known.

We know that value of

$\cos (x - y) - \cos (x + y) = 2\sin x\sin y$ …………………………………...(2)

Put $x = 80$and $y = 40$in the equation (2) ,we get

\[

2\sin {80^0}\sin {40^0} = \cos ({80^0} - {40^0}) - \cos ({80^0} + {40^0}) \\

\Rightarrow 2\sin {80^0}\sin {40^0} = \cos ({40^0}) - \cos ({120^0}) \\

\]

We know that $\cos \left( {{{180}^0} - \theta } \right) = - \cos \theta $

Put $\theta = {60^0}$ in above $ \Rightarrow \cos {120^0} = \cos \left( {{{180}^0} - {{60}^0}} \right) = - \cos {60^0} = - \dfrac{1}{2}$

\[ \Rightarrow 2\sin {80^0}\sin {40^0} = \cos ({40^0}) - \cos ({120^0}) = \cos ({40^0}) + \dfrac{1}{2}\] …………………(3)

Multiplying expression (1) with $\dfrac{2}{2}$ and rearranging, we get

$\dfrac{{2\sin {{80}^0}\sin {{40}^0}\sin {{60}^0}\sin {{20}^0}}}{2}$

Using equation (3) in above, we get

$\left( {\cos {{40}^0} + \dfrac{1}{2}} \right)\dfrac{{\sin {{60}^0}\sin {{20}^0}}}{2}$

Using $\sin {60^0} = \dfrac{{\sqrt 3 }}{2}$ in above,

$ \Rightarrow \left( {\cos {{40}^0} + \dfrac{1}{2}} \right)\dfrac{{\sqrt 3 }}{4}\sin {20^0}$

$ \Rightarrow \dfrac{{\sqrt 3 }}{8}\left( {2\sin {{20}^0}\cos {{40}^0} + \sin {{20}^0}} \right)$ …………………………………………………...(4)

We know that value of

$\sin (x + y) + \sin (x - y) = 2\sin x\cos y$ ……………………………………………...(5)

Put $x = 20$and $y = 40$in the equation (5), we get

\[

2\sin {20^0}\cos {40^0} = \sin ({20^0} + {40^0}) + \sin ({20^0} - {40^0}) \\

\Rightarrow 2\sin {20^0}\sin {40^0} = \sin ({60^0}) + \sin ( - {20^0}) \\

\]

We know that $\sin \left( { - \theta } \right) = - \sin \theta $

Put $\theta = {20^0}$ in above gives $\sin \left( { - {{20}^0}} \right) = - \sin {20^0}$

\[ \Rightarrow 2\sin {20^0}\sin {40^0} = \sin ({60^0}) - \sin ({20^0}) = \dfrac{{\sqrt 3 }}{2} - \sin ({20^0})\] ……………………………….(6)

Using equation (6) in (4), we get

\[

\dfrac{{\sqrt 3 }}{8}\left( {2\sin {{20}^0}\cos {{40}^0} + \sin {{20}^0}} \right) = \dfrac{{\sqrt 3 }}{8}\left( {\dfrac{{\sqrt 3 }}{2} - \sin {{20}^0} + \sin {{20}^0}} \right) \\

\Rightarrow \dfrac{{\sqrt 3 }}{8}\left( {\dfrac{{\sqrt 3 }}{2}} \right) = \dfrac{3}{{16}} \\

\]

Therefore, the value of expression (1) is $\dfrac{3}{{16}}$.

Hence option $(C)$ $\dfrac{3}{{16}}$ is the correct answer.

Note: Always remember trigonometric sum to product and product to sum formula. Modifications may need to be performed in the expressions like above in order to use these identities. These modifications should never alter the value of the original expression. Try to convert the expression in problems of above type into known trigonometric ratio values.

Given in the problem, we need to find value of the expression

$\sin {20^0}\sin {40^0}\sin {60^0}\sin {80^0}$ …………………………….. (1)

We need to group terms so that using a product to sum trigonometric formula gives angles whose trigonometric value is known.

We know that value of

$\cos (x - y) - \cos (x + y) = 2\sin x\sin y$ …………………………………...(2)

Put $x = 80$and $y = 40$in the equation (2) ,we get

\[

2\sin {80^0}\sin {40^0} = \cos ({80^0} - {40^0}) - \cos ({80^0} + {40^0}) \\

\Rightarrow 2\sin {80^0}\sin {40^0} = \cos ({40^0}) - \cos ({120^0}) \\

\]

We know that $\cos \left( {{{180}^0} - \theta } \right) = - \cos \theta $

Put $\theta = {60^0}$ in above $ \Rightarrow \cos {120^0} = \cos \left( {{{180}^0} - {{60}^0}} \right) = - \cos {60^0} = - \dfrac{1}{2}$

\[ \Rightarrow 2\sin {80^0}\sin {40^0} = \cos ({40^0}) - \cos ({120^0}) = \cos ({40^0}) + \dfrac{1}{2}\] …………………(3)

Multiplying expression (1) with $\dfrac{2}{2}$ and rearranging, we get

$\dfrac{{2\sin {{80}^0}\sin {{40}^0}\sin {{60}^0}\sin {{20}^0}}}{2}$

Using equation (3) in above, we get

$\left( {\cos {{40}^0} + \dfrac{1}{2}} \right)\dfrac{{\sin {{60}^0}\sin {{20}^0}}}{2}$

Using $\sin {60^0} = \dfrac{{\sqrt 3 }}{2}$ in above,

$ \Rightarrow \left( {\cos {{40}^0} + \dfrac{1}{2}} \right)\dfrac{{\sqrt 3 }}{4}\sin {20^0}$

$ \Rightarrow \dfrac{{\sqrt 3 }}{8}\left( {2\sin {{20}^0}\cos {{40}^0} + \sin {{20}^0}} \right)$ …………………………………………………...(4)

We know that value of

$\sin (x + y) + \sin (x - y) = 2\sin x\cos y$ ……………………………………………...(5)

Put $x = 20$and $y = 40$in the equation (5), we get

\[

2\sin {20^0}\cos {40^0} = \sin ({20^0} + {40^0}) + \sin ({20^0} - {40^0}) \\

\Rightarrow 2\sin {20^0}\sin {40^0} = \sin ({60^0}) + \sin ( - {20^0}) \\

\]

We know that $\sin \left( { - \theta } \right) = - \sin \theta $

Put $\theta = {20^0}$ in above gives $\sin \left( { - {{20}^0}} \right) = - \sin {20^0}$

\[ \Rightarrow 2\sin {20^0}\sin {40^0} = \sin ({60^0}) - \sin ({20^0}) = \dfrac{{\sqrt 3 }}{2} - \sin ({20^0})\] ……………………………….(6)

Using equation (6) in (4), we get

\[

\dfrac{{\sqrt 3 }}{8}\left( {2\sin {{20}^0}\cos {{40}^0} + \sin {{20}^0}} \right) = \dfrac{{\sqrt 3 }}{8}\left( {\dfrac{{\sqrt 3 }}{2} - \sin {{20}^0} + \sin {{20}^0}} \right) \\

\Rightarrow \dfrac{{\sqrt 3 }}{8}\left( {\dfrac{{\sqrt 3 }}{2}} \right) = \dfrac{3}{{16}} \\

\]

Therefore, the value of expression (1) is $\dfrac{3}{{16}}$.

Hence option $(C)$ $\dfrac{3}{{16}}$ is the correct answer.

Note: Always remember trigonometric sum to product and product to sum formula. Modifications may need to be performed in the expressions like above in order to use these identities. These modifications should never alter the value of the original expression. Try to convert the expression in problems of above type into known trigonometric ratio values.

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Name the Largest and the Smallest Cell in the Human Body ?

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

A ball impinges directly on a similar ball at rest class 11 physics CBSE

Lysosomes are known as suicidal bags of cell why class 11 biology CBSE

Two balls are dropped from different heights at different class 11 physics CBSE

A 30 solution of H2O2 is marketed as 100 volume hydrogen class 11 chemistry JEE_Main

A sample of an ideal gas is expanded from 1dm3 to 3dm3 class 11 chemistry CBSE